The military balance 2019 (Routledge, 2019)
The Military Balance 2014 contains region-by-region analysis of the major military and economic developments affecting defence and security policies and the trade in weapons and other military equipment. Detailed entries describe the military capabilities of 171 countries, displaying key equipment inventories and defence economics. Comprehensive tables detail major training activities, UN and non-UN deployments, and international comparisons of defence expenditure and military personnel.